A Note on “The Equivalence of Integer Programs to Constrained Recursive Systems” - Kafpauf, Charles H. (Management Science, 1975)
Nanda proposes (Management Science, March, 1973) an algorithm for transforming a general integer programming problem with elements 0, +1, or −1 in the constraint matrix into an equivalent one in which the primary constraints are supposed to form an integral, recursive substitution system. Unfortunately, the algorithm does not always guarantee this. This note explains why and gives the addition which must be made to the algorithm to yield the results desired by Nanda.